Evaluasi Rekam Medis Elektronik Bagian Coding Rawat Inap RSUD K.R.M.T Wongsonegoro Kota Semarang - Septina Dwi Indrawati; Ida Nurmawati; Indah Muflihatin; Syaifuddin Syaifuddin (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
RSUD K.R.M. T Wongsonegoro The city of Semarang became one of the type B hospitals in the city of Semarang, which have applied the electronic medical record gradually the application of electronic medical records assessed as an effort to improve the quality of services increasing patient satisfaction improves the documentation accuracy reduces clinical error and speeds up patient data access. (Billy Maria in Andriani DKK 2017). One of the service units that require the speed, accuracy and accuracy of access to patient data is the coding part of the hospitalization of the person who handled the medical record and coding (PJRM). In its implementation, there were constraints that made the officers less satisfied with RME. The purpose of this research is to evaluate RME implementation using the PIECES method (performance, information, economic, control, efficiency, service). This type of research is qualitative research, by conducting observation methods and interviews to PJRM officers. The results of RME evaluation conducted using the PIECES method on the performance/performance aspect, RME has already produced a good performance. Based on information/information aspect, RME can provide accurate information quality, according to user needs, and easy to understand. Based on Economy/economy, RME has the value to be integrated with one hospital and have qualified resource. Based on Control/control aspect, RME has good integrity and security because it comes with username and password, has different permissions. Based on the Efficiency/data efficiency aspects of RME can be easily learned, operated, and processed. Based on the Service/service aspect: RME users feel that RME provides convenience for RME users. In conclusion, RME in the coding part of inpatient is good enough in terms of Performance, Information, Economy, Control, Efficiency and Control. The advice that can be given is to make improvements and development on RME to avoid errors, regulatory or regulation regarding steps when errors occur, as well as conducting socialization or training to RME users.